2021
DOI: 10.3390/ijerph18020797
|View full text |Cite
|
Sign up to set email alerts
|

As the Pandemic Progresses, How Does Willingness to Vaccinate against COVID-19 Evolve?

Abstract: Controversy around the safety and efficacy of COVID-19 vaccines may lead to low vaccination rates. Survey data were collected in April and August 2020 from a total of 2343 Australian adults. A quarter (n = 575, 24%) completed both surveys. A generalized linear mixed model analysis was conducted to determine whether willingness to vaccinate changed in the repeated sample, and a multinominal logistic regression was conducted in all participants to determine whether willingness to vaccinate was associated with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
100
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(122 citation statements)
references
References 21 publications
15
100
5
2
Order By: Relevance
“…This trend was similar to the findings of previous studies in developed countries. 14,19,24,25 Notably, we found a gender gap in the associations of age and education level with willingness to get the COVID-19 vaccine: men who were older or had a higher level of education were more willing to get the vaccine, whereas women aged 30-49 years and those with a higher level of education were less willing to get the vaccine. Other factors showed similar trends for men and women: for both men and women, a higher likelihood of being willing to get the COVID-19 vaccine was observed in married participants, those with a higher annual household income, those who had an underlying disease, those who currently smoked, those who had been vaccinated against influenza during the current season, and those with a fear of COVID-19 transmission.…”
Section: Discussionmentioning
confidence: 77%
“…This trend was similar to the findings of previous studies in developed countries. 14,19,24,25 Notably, we found a gender gap in the associations of age and education level with willingness to get the COVID-19 vaccine: men who were older or had a higher level of education were more willing to get the vaccine, whereas women aged 30-49 years and those with a higher level of education were less willing to get the vaccine. Other factors showed similar trends for men and women: for both men and women, a higher likelihood of being willing to get the COVID-19 vaccine was observed in married participants, those with a higher annual household income, those who had an underlying disease, those who currently smoked, those who had been vaccinated against influenza during the current season, and those with a fear of COVID-19 transmission.…”
Section: Discussionmentioning
confidence: 77%
“…Vaccine hesitancy rate can vary across countries [20][21][22][23][24][25][26][27][28][29][30][31]. An online survey conducted in Turkey (n = 3936) and in the UK (n = 1088) throughout May 2020 found that COVID-19 vaccine hesitancy was significantly higher in Turkey [20].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study examining real-world uptake of a COVID-19 vaccine in a setting of unrestricted availability within a community, culminating in a vaccination rate of 89.8% in the military unit studied. Currently published data on COVID-19 vaccine uptake is predominantly based on hypothetical surveys of different populations, prior to vaccine emergency use authorization and availability [3,6,[11][12][13][14]. While large-scale strategies to improve COVID-19 vaccine uptake have been discussed [4,6,15], the value of informing individuals and groups at the community level cannot be understated [6].…”
Section: Discussionmentioning
confidence: 99%